Ura pouka v šolski knjižnici s knjižničarko Mrcino - Belak, Laura (Šolska knjižnica, 2016)
During a Slovenian Language lesson, we visited the school library after discussing the book The Legend of Spud Murphy by Eoin Colfer. During the discussion of the book, the pupils were acquainted with the prose reading sheet, on which they have to write down the basic information about the book they have read and analyse it from the aspect of content, form and language. The pupils insert the filled-out reading lists into their reading folders, which help them to tell stories under the reading badge project, and practise the skill of oral presentations. During the lesson in the school library, the librarian presented to the pupils the process of creating a book and how the book passes from the author to the shelf of the school library and eventually to the reader. Afterwards, the pupils tried their hand at making their own book, for which they had to bear in mind the formal properties of books.
Keywords: knjižnična vzgoja; medpredmetno povezovanje; osnovne šole; slovenščina; šolske knjižnice